Pengaruh Penerapan Akuntansi Pertanggungjawaban Terhadap Efektivitas Pengendalian Biaya pada UMKM yang Ada di Kabupaten Pasuruan - Saputri, Agesha Aprilia Diani; Maslichah, Maslichah; Mahsuni, Abdul Wahid (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The aimed of this research is to elucidate the influence of organizational structure, budget system, control system and accountability on cost control accounting in UMKM. This research used to UMKM in Pasuruan district. The methodological approach employed is multiple linear regression analyze. The findings indicated by organizational structure, budgeting systems, control mechanisms, and accountability frameworks significantly influence the implementation of accountabilities in accounting and the efficacy of cost control within Pasuruan Regency. The organizational structure variable has a significant affected in the cost control effectiveness in UMKM in Pasuruan district. Specifically, the organizational structure variable exerts a substantial effect on cost control effectiveness in UMKM in Pasuruan. Similarly, the budgeting system variable also demonstrates a significant impact on cost control efficiency in these UMKM. Additionally, the control mechanism variables markedly influence the cost control effectiveness in the UMKM of Pasuruan Regency.Keywords : Cost control accounting, structure organization, budget system, control system, and accountability